Hydrothermally Synthesized Copper Gallium Delafossite Nanoflakes for (Photo)Electrocatalytic Water Splitting. (7th July 2017) - Mohan, Swati; Mao, Yuanbing
Abstract : Delafossite CuGaO2 nanoflakes with different sizes and thicknesses have been controllably synthesized by a hydrothermal method including various amounts of surfactant sodium dodecyl sulfate (SDS) at 190 o C for 60 h for the first time and compared with CuGaO2 microplates synthesized under the same conditions without adding SDS. The synthesized CuGaO2 nanoflakes and microplates were first thoroughly characterized by powder X-ray diffraction, SEM, EDX, XPS, FT-IR, UV-Vis and BET surface area measurements. Moreover, their electrocatalytic and photoelectrocatalytic performance for oxygen evolution reaction (OER) in 0.5 M KOH electrolyte versus Ag/AgCl along with their stability were studied as a cost-effective and active electrode material for water splitting application. Based on cyclic voltammetry and electrochemical impedance spectroscopy measurements, the onset potential, current density, Tafel slope, charge transfer resistance, and stability were obtained and compared. It was demonstrated that the delafossite CuGaO2 nanoflakes synthesized in the presence of SDS at certain concentrations showed better (photo)electrocatalytic performance and stability for OER than those synthesized without the presence of surfactant SDS.